Potentials and Challenges of Pervasive Sensing in the Intensive Care Unit - Davoudi, Anis; Shickel, Benjamin; Tighe, Patrick James; Bihorac, Azra; Rashidi, Parisa (Frontiers in Digital Health, 2022)
Patients in critical care settings often require continuous and multifaceted monitoring. However, current clinical monitoring practices fail to capture important functional and behavioral indices such as mobility or agitation. Recent advances in non-invasive sensing technology, high throughput computing, and deep learning techniques are expected to transform the existing patient monitoring paradigm by enabling and streamlining granular and continuous monitoring of these crucial critical care measures. In this review, we highlight current approaches to pervasive sensing in critical care and identify limitations, challenges, and opportunities in this emerging field.